Interocular suppression in children with deprivation amblyopia. (April 2017) - Hamm, Lisa; Chen, Zidong; Li, Jinrong; Black, Joanna; Dai, Shuan; Yuan, Junpeng; Yu, Minbin; Thompson, Benjamin
Highlights: Contrast balancing can minimize interocular suppression in deprivation amblyopia. Stronger suppression was associated with later cataract removal. Binocular treatment may be feasible to attempt in deprivation amblyopia. Abstract: In patients with anisometropic or strabismic amblyopia, interocular suppression can be minimized by presenting high contrast stimulus elements to the amblyopic eye and lower contrast elements to the fellow eye. This suggests a structurally intact binocular visual system that is functionally suppressed. We investigated whether suppression can also be overcome by contrast balancing in children with deprivation amblyopia due to childhood cataracts. To quantify interocular contrast balance, contrast interference thresholds were measured using an established dichoptic global motion technique for 21 children with deprivation amblyopia, 14 with anisometropic or mixed strabismic/anisometropic amblyopia and 10 visually normal children (mean age mean = 9.9 years, range 5–16 years). We found that interocular suppression could be overcome by contrast balancing in most children with deprivation amblyopia, at least intermittently, and all children with anisometropic or mixed anisometropic/strabismic amblyopia. However, children with deprivation amblyopia due to early unilateral or bilateral cataracts could tolerate only very low contrast levels to the stronger eye indicating strong suppression. Our results suggest that treatment options reliant on contrast balanced dichoptic presentation could be attempted in a subset of children with deprivation amblyopia.